Atlas of furniture design : Mateo Kries. - Kries, Mateo, 1974-; Eisenbrand, Jochen, 1970- (Weil am Rhein : Vitra Design Museum, 2019)
From the Vitra Design Museum a 1,000-page book that will deliver the most comprehensive overview on the history of furniture design ever published The publication will document some 1,691 objects, 550 of them accompanied by detailed texts. The project has involved a team of over 70 authors and features roughly 2,595 images, from high-quality object photographs to reproductions of historical documents such as brochures, patents, interiors or reference works in art or architecture. The basis for the Atlas of Furniture Design is the furniture collection held by the Vitra Design Museum, one of the largest of its kind in the world with more than 6,400 pieces of furniture as well as the estates of such design legends as Charles & Ray Eames, Verner Panton, Alexander Girard, George Nelson and others. The collection comprises pieces by the most significant designers and manufacturers of the past 200 years. It includes early industrial furniture in bentwood or metal, Art Nouveau and Secessionist pieces, protagonists of classical modernism like Le Corbusier, Gerrit Rietveld, Charlotte Perriand or Marcel Breuer, postwar figures such as Finn Juhl, Gilbert Rohde, Pierre Paulin or Gae Aulenti but also postmodern and contemporary designers like Philippe Starck, Marcel Wanders or Konstantin Grcic
Keywords: design; toegepaste kunst